Problematika Terhadap Batas Waktu Perlindungan Saksi Oleh Lpsk Dalam Perkara Pidana - Muhammad Ghazali Rahman (Jurnal Penegakan Hukum Indonesia, 2021)
This study aims to determine the time limit of protection provided by LPSK clearly to witnesses who are undergoing the examination process and also to find out whether LPSK has provided protection in accordance with what is currently in effect. The type of research used is normative legal research, namely research to obtain legal materials by analyzing and collecting legal materials related to the issues discussed. (1) The protection efforts that will be given to witnesses regarding a limit on when the protection starts and ends of witness protection byLPSK must be optimized so that witnesses who give their statements in order to seek a truth are deemed necessary to clearly pay attention to the time limit for witness protection. (2) Law No. 31 of 2014 on LPSK, especially regarding the time limit for protection, is still considered not maximal and is considered not sufficient to guarantee the witness's sense of trust in LPSK. Weaknesses like this become an obstacle if the witness wants to give information without knowing the time limit for the protection clearly. Of course, there needs to be a complete and more perfect arrangement, presumably the right to witness protection needs to be accommodated in principles, general provisions, types of punishment and other substances.